Understanding Chinese consumer behaviour regarding sustainable diets: Intention to reduce meat consumption and adopt protein alternatives - Zhang, Yuchen (2022)
With the alarming global challenges of climate change, water scarcity, population growth and food security, adopting a sustainable diet can be considered as one of the strategies to help our planet. China represents 19% of the global population, and little research has conducted to date to understand sustainable diet adoption for Chinese consumers. This study aimed to explore Chinese consumers' intentions towards adopting a sustainable diet – reducing meat intake and adopting meat alternatives. An online questionnaire was disseminated to recruited 778 consumers in Shanghai (China). Although limited information is available in China regarding sustainability, the results suggest that Chinese consumers are generally aware of sustainable diets and have good environmental awareness to a range of food behaviours and food items. However, they tend to underestimate the environmental impact of different types of meat. When exploring different consumer segmentations, non-meat eaters had higher environmental awareness than meat eaters, indicating environmental awareness could be one of the motivating factors determining whether or not consumers would eat meat. However, when looking into the three meat eater groups, no such difference was found, indicating those consumers who choose to consume meat, had lower environmental awareness. In general, Chinese consumers’ meat attachments scores were relatively lower than other countries reported in literature. Consumers showing low meat attachment tended to have higher behavioural control and personal norm in relation to reducing their meat consumption, however, subjective norm does not affect consumers’ meat attachment. The majority of the consumers indicated they were willing to reduce meat consumption, and identified food safety, environmental and health benefits as their strongest motivators, while animal welfare was identified as the least motivating factor. When asking consumers option on adopting three meat alternatives (meat substitutes, edible insects, and cultured meat), consumers were more willing to adopt meat substitutes and cultured meat than edible insects. Food safety and environment indicated as primary motivational factors for adopting the three meat alternatives, indicating food safety and environmental benefit are the two key considerations when promoting meat alternatives. This study highlighted valuable information regarding Chinese consumers’ intention to reduce their meat intake and adopt meat alternatives, further studies exploring the effect of cross cultural impact sustainable diet are required.